Pengaruh Lima Dimensi Kualitas Layanan terhadap Kepuasan Pasien di Klinik Gigi X di Jakarta Barat - Golahi, Gilbert; Mulyadi, Elita; Suwigyoputro, Stefano Giovani Handoko; Erlilis, Erlilis (Syntax Literate, 2025)
The quality of service at private dental clinics plays an important role in building patient satisfaction. The SERVQUAL model is used to evaluate five dimensions of service quality: tangible, reliability, responsiveness, assurance, and empathy. This study aims to analyze the influence of the five dimensions of SERVQUAL on patient satisfaction at Dental Clinic X, West Jakarta, and identify the most influential dimensions. Descriptive analytical research with a cross-sectional approach was conducted on 100 patients through purposive sampling. The inclusion criteria include patients aged ≥18 years who have undergone treatment at X Dental Clinic for the past year. Data were collected using the SERVQUAL questionnaire and Customer Satisfaction Index on a Likert scale of 1–5. Gap analysis and t-test were carried out using SPSS version 29.02. As a result, the tangible dimension has the highest gap of 0.70 in the aspect of modern equipment, while responsiveness has the lowest gap of 0.30 in the aspect of service time notification. All dimensions have a positive gap value, indicating that the quality of service has met or exceeded patient expectations. The average value of the customer satisfaction index is 3.26 with a standard deviation of 0.078. The results of the t-test showed that all dimensions of SERVQUAL had a significant effect on patient satisfaction (p < 0.05). Conclusion, All dimensions of service quality have an influence on the quality of service in clinic X. This study provides strategic insights to improve the quality of dental clinic services and maintain patient loyalty.